2005
DOI: 10.1002/marc.200590008
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Macromol. Rapid Commun. 5/2005

Abstract: Cover: The cover picture shows the molecular architecture and the absorption and emission spectra of a novel rod-like polyyne polymer comprised of an electron-rich platinum framework and an electron-accepting silole unit that features an alternating donor-p-acceptor (D-p-A) type structural motif. This polymer exhibits a very low band gap and interesting optoelectronic properties.Further details can be found in the Communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Silole-based polymers P1 and P2 emit orange light with emission maxima located at 612 and 623 nm, while P3 and P4 emit red light with emission maxima located at 688 and 657 nm. All of these polymers exhibit large Stokes' shifts of ∼80À110 nm, which are not unusual for silicon-containing polymers, 46,76 and may possibly be due to eximer emission. 77,78 However, when electron-deficient polymer P5 is excited at the short-wavelength (392 nm) or at the long-wavelength absorption maximum (681 nm), only very weak, broad emissions having shapes similar to the absorption spectra are observed with maxima at 439, 539 nm or 793, 913 nm, respectively.…”
Section: ' Results and Discussionmentioning
confidence: 89%
“…Silole-based polymers P1 and P2 emit orange light with emission maxima located at 612 and 623 nm, while P3 and P4 emit red light with emission maxima located at 688 and 657 nm. All of these polymers exhibit large Stokes' shifts of ∼80À110 nm, which are not unusual for silicon-containing polymers, 46,76 and may possibly be due to eximer emission. 77,78 However, when electron-deficient polymer P5 is excited at the short-wavelength (392 nm) or at the long-wavelength absorption maximum (681 nm), only very weak, broad emissions having shapes similar to the absorption spectra are observed with maxima at 439, 539 nm or 793, 913 nm, respectively.…”
Section: ' Results and Discussionmentioning
confidence: 89%
“…For the soluble silole-containing polyplatinayne P48, the E g value is impressive at 2.10 eV, again due to the intramolecular D-A interaction between the electron-rich metal-ethynyl unit and the electron-poor silole ring, 55 and it is significantly lowered by ca. 1.0 eV relative to P52 (ca.…”
Section: Effect Of a Donor-acceptor Structural Motifmentioning
confidence: 99%
“…In 2005, Wong et al reported the synthesis and characterization of the first examples of a soluble, thermally stable, low band gap, silole-containing platinum (II) polyynes 22 and the corresponding model monomer 21 [23]. Inclusion of the metal ethynyl unit resulted in intense pep* transitions (l max ¼ 470 and 504 for 21 and 22, respectively) suggesting an intramolecular interaction between metal ethynyl units and silole rings that substantially perturbs the electronic structure of the parent silole unit [23]. In contrast, the quantum efficiencies dramatically decreased from the model compound 21 (40%) to that of the polymer 22 (10%).…”
Section: Silole-containing Polymers and Chromophoresmentioning
confidence: 99%